STUDI KASUS SUPERVISI AKADEMIK DI SMP NEGERI 3 TAMBELANGAN KECAMATAN TAMBELANGAN KABUPATEN SAMPANG TAHUN PELAJARAN 2018/2019 - Mohamad Sumarfakun (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
The study is aimed at knowing, understanding and describing in detail the planning and implementation of the school program and the follow-up activity of academic supervision at SMPN 3 Tabelangan Sampang Madura. The approach of the study makes use of a qualitative approach through the case study. The research subjects are school principal, vice-principal, 2 senior teachers, and 10 PNS teachers and honorarium teachers. The data are collected through observation, interviews, and documentation. The result of the study shows that the planning of the school program which is conducted by the school principal, vice-principal, and senior teachers, does not involve all related elements that affect the success of the academic supervision program. The implementation of academic supervision which involves school principal and senior teachers uses the direct method. The follow-up activity of academic supervision is merely giving founding and reinforcement to the teachers. Based on the result of the study, it is found that the implementation of academic supervision conducted by the school principal has not been reached effectively in improving the better teaching result.